Impact and meaning of the postponement of Tokyo 2020 from an athlete perspective - Cerulo, I. (Olimpianos - Journal of Olympic Studies, 2020)
Rescheduling the Olympic Games was an unprecedented decision, justified by the rapid contagion of a novel coronavirus (COVID-19) and the need to prioritize the health, safety, and well-being of all people expected to attend the Games. The group arguably most affected by this decision is the group that is at the heart of the Olympic Games and the Olympic Movement: the athletes. The postponement of Tokyo 2020 generated uncertainty for athletes, as well as their support networks, something even more intensely experienced by athletes who are still in the qualification process. In all, this unprecedented disruption to athlete`s routines and daily expectations leads to feelings of loss of control and stress. The manner in which athletes cope effectively with change-events plays a significant role in their performance and even the longevity of their athletic careers. This paper explores the complexities of some of the expectations athletes have had to redefine, as well as the impact of this process in itself, from an athlete`s perspective.